High Quantum Yield Blue InP/ZnS/ZnS Quantum Dots Based on Bromine Passivation for Efficient Blue Light‐Emitting Diodes. Issue 15 (23rd May 2022) - Zhang, Wenda; Tan, Yangzhi; Duan, Xijian; Zhao, Fangqing; Liu, Haochen; Chen, Wei; Liu, Pai; Liu, Xiaogang; Wang, Kai; Zhang, Zhikuan; Sun, Xiao Wei
Abstract: Red and green InP quantum dots (QDs) already have been demonstrated with excellent luminescence performance closing the gap with CdSe‐based QDs. However, the performance of blue InP QDs still lags behind that of red and green QDs. For blue InP QDs synthesized by aminophosphine and zinc iodide, the inherent I – possesses weak passivation ability. By introducing Br – with a smaller ion radius and larger binding energy, the quantum yield of blue InP QDs is increased from 54% to 93%, which is the highest value reported so far. Meanwhile, the long‐chain 1‐dodecanethiol is replaced by the short‐chain 1‐octanethiol through ligand exchange to increase the carrier injection efficiency. The blue quantum dot light‐emitting diodes (QLEDs) made of these QDs showed an external quantum efficiency of 2.6%, which is notably the highest blue InP QLED reported so far. Abstract : In this paper, Br − passivation of the surface of InP/ZnS/ZnS quantum dots (QDs) was carried out. The quantum yield of the InP/ZnS/ZnS QDs increased from 54% to 93%. Meanwhile, the long‐chain 1‐dodecanethiol is replaced by the short‐chain 1‐octanethiol to increase the carrier injection efficiency. The quantum dot light‐emitting diode showed an external quantum efficiency of 2.6%, which is also the highest value reported to date.